PENGARUH MEDIA PEMBELAJARAN TERHADAP EFEKTIFITAS PEMBELAJARAN FIQIH SISWA : Volume 1, Nomor 1 (2024) - Gustiansyah alfanka (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the effect of learning media on the effectiveness of students’ fiqh learning. Data collection techniques in this research are questionnaires, interviews and documentation. The data analysis technique uses the chi square formula. Based on the calculation of the posttest average difference test. The results obtained were a tcount value of 1.974 and ttable at the 5% significance level of 1.739. This calculation shows that tcount > ttable so that the proposed hypothesis is accepted. This shows that the use of learning media influences the effectiveness of students’ fiqh learning